The effects of vocabulary knowledge in L2 semantic lexical engagement: The case of adult learners of English as a second language - García-Castro, Verónica (Indonesian Journal of Applied Linguistics, 2020)
There is evidence that L1 and L2 lexical engagement of novel items occurs in adulthood. However, previous studies have not addressed the effects of individual differences on that engagement. Hence, it is unknown how individual differences may influence semantic lexical engagement gains in L1 and L2 adult learners. This study investigates the effects of pre-existing vocabulary knowledge on L2 semantic lexical engagement of recently learned novel words. A semantic priming experiment, across two consecutive days, was conducted.  A group of advanced L2 learners (n=26) and L1 learners (n=26) participated in the study. They were trained on pseudowords acting as verbs (n=7) and nouns (n=7). Vocabulary knowledge was measured via an online vocabulary size test.  On day one, participants learned the meaning of the pseudowords via reading 12 repetitions of the novel words embedded into English sentences. Immediately, after the reading session, participants undertook surprise recognition and recall vocabulary post-tests. On day two, participants took part in a semantic lexical decision task (LDT) with priming to test L2 semantic lexical engagement of the novel words learned on day one. The data were analysed through a series of general and linear mixed-effects models. The results showed that L1 and L2 participants engaged the meaning of the recently learned novel words. Previous vocabulary knowledge predicted faster recognition of semantic related and unrelated primes in the LDT task. It is concluded that L1 and L2 adult learners lexically engaged the meaning of the recently learned words and that vocabulary size is a predictor of L2 semantic lexical engagement of novel words within the conditions of this study. The empirical findings provide a new understanding of the role vocabulary knowledge on L1 and L2 semantic lexical engagement of novel words.